An alternative strategy to detect bacterial contamination in milk and water: a newly designed electrochemical biosensor - KOCA, ATIF; SESAL, NÜZHET CENK (SPRINGER, 2020)
The detection of acyl homoserine lactones (AHLs) can render their use as biomarkers and it may provide a chance to fight against food contamination and bacterial pathogens. For this purpose, in this study, an electrochemical biosensor was designed for the detection of AHLs to prevent harmful bacterial activities. The electrochemical biosensor was constructed by coating of zinc phthalocyanine bearing stabile TEMPO radical groups (TEMPO-ZnPc) on a glassy carbon electrode (GCE) and it was utilized for AHL detection. GCE/TEMPO-ZnPc electrode acted as amperometric biosensor for 3-oxo-C-12-HSL, C-10-HSL, C-8-HSL, C-6-HSL, and C-4-HSL molecules, the sensor electrode only selectively sensed 3-oxo-C-12-HSL molecule among the tested AHL molecules. The sensing measurements showed that 3-oxo-C-12-HSL produced by Pseudomonas aeruginosa was detected between 2.32 x 10(-6) and 39.9 x 10(-6) mol dm(-3) concentrations with 1.8 x 10(-6) mol dm(-3) limit of detection (LOD) in water. Additionally, the electrochemical biosensor was successfully applied for the detection of AHLs in milk samples. The sensing results indicated that GCE/TEMPO-ZnPc electrode can be used as rapid, sensitive, and selective biosensor for the detection of foodborne pathogens.
Keywords: Foodborne pathogens; Quorum sensing; AHL; Biosensor; Food contamination; Biofilm; ACYL-HOMOSERINE-LACTONES; RAPID DETECTION; ELECTRODE MODIFICATION; VIRULENCE FACTORS; QUORUM; SENSORS; PHTHALOCYANINE; MOLECULES; PATHOGENS; POLYMERS